Carbon stocks in major cashew growing soils of coastal Karnataka, India - K.S. Anil Kumar, M. Lalitha, R. Srinivasan, A. Natarajan (Journal of Plantation Crops, 2019)
This study was taken up to assess the soil organic carbon (SOC) stock under cashew plantations in different management conditions viz., natural (cashew mixed with forest trees and cashew in scrub land conditions) and intensive management (research stations) in regions/locations of coastal Karnataka. Profile study was undertaken and six major soil series were identified. Horizon-wise soil samples were collected from different layers of soil profiles and the major soil properties viz., bulk density, pH, EC, particle size distribution and SOC were determined using standard laboratory procedures. The SOC stock was high in surface soils (2.0 to 8.23 kg C m-2) compared to subsoils (0.08 to 3.28 kg C m-2) and it decreased with depth. The maximum SOC was found in mixed forest land use system followed by cashew plantation in scrub land and in research farm. The SOC stock in different depths (0-30, 30-100 and 0-100 cm) of the soils varied from 2.37 to 9.70 kg C m-2 and 1.48 to 5.69 kg C m-2, respectively. Result indicated that cashew plantation under natural management has more SOC stock and high carbon sequestration potential-than intensively managed cashew plantations.